Associations between sedentary behaviour patterns and depression among people aged 60 and older in Hebei Province of China - Wang, Jiaqi; Li, Ruiqiang; Zhang, Limin; Gao, Xian; Zhou, Meiqi; Zhang, Xinjing; Ma, Yuxia (BMC public health, 2022)
Sedentary behaviours (SBs) are now considered a risk factor for depression. Older adults are sedentary most of the time and are at a high risk of depression. However, not all types of SBs have adverse effects on mental health. Passive SBs (such as watching TV) increase the risk of depression, whereas mentally active SBs (such as using the internet and reading) decrease the risk of depression. The aim of this study was to explore the associations between type of SBs (i.e., passive and mentally active SBs) and depression among people aged 60 years and older in the Hebei Province of China. This cross-sectional study used data from the baseline survey of the Community-based Cohort Study on Nervous System Diseases. A total of 2679 older adults aged ≥60 years from the Hebei Province of China were included in this study. The type and time spent on SBs were self-reported. Watching TV was defined as a passive SB, whereas internet use, reading, and social SBs (including communicating with others and playing chess) were defined as mentally active SBs. Depression was evaluated using the Geriatric Depression Scale. The maximal possible score was 30 points, and ≥ 11 points indicated depression. Logistic regression analysis was used to assess the relationship between SBs and depression. Covariates included sex, age, education, employment, smoking, alcohol consumption, sleep duration, domestic work, physical exercise, body mass index (BMI), and chronic diseases. At baseline, the participants who spent two or more hours and 0 h on passive SBs (i.e., TV viewing) had a greater risk of depression (=0 h: adjusted OR = 2.09, 95% CI = 1.18-3.76; 2-3 h: OR = 2.21, 95% CI = 1.16-4.16; > 3 h: OR = 3.59, 95% CI = 1.93-6.68) than the participants who spent 1-2 h on passive SBs. The participants who spent > 1 h on mentally active SBs had a lower risk of depression (adjusted OR = 0.26, 95% CI = 0.06-0.71) than the participants who did not engage in mentally active SBs. Not all mentally active SBs were linked to depression. The participants who engaged in social SBs had a lower risk of depression (adjusted OR: 0.24, 95% CI: 0.06-0.66) than the participants who did not engage in social SBs. Spending 2 h or more per day on passive SBs (watching TV) was associated with a high risk of depression among people aged 60 years and older in the Hebei Province of China. Mentally active SBs (predominantly social SBs) could reduce the risk of depression. Some participants with depression probably did not watch TV. These findings suggested that spending more time on social SBs (such as communicating with others and playing chess) rather than watching TV may have important public health implications for preventing and managing depression among older Chinese adults. Moreover, society should attend to the mental health of elderly adults who do not watch TV as they may be more prone to suffer from depressive symptoms.